Investigation on the Performance of a Portable Power Generation System with a Low-Cost Vertical Axis Wind Turbine - Basar, M. F.; Norazizi, A. M.; Mustaffa, I.; Colin, C. T.; Mirin, S. N. S.; Jano, Z. (Engineering, Technology & Applied Science Research, 2021)
The purpose of this project was to develop an innovative, small-scale, and portable vertical axis wind turbine for power generation. The wind turbine was simple in design and economical. Wind speeds ranging from 2.0ms-1 to 7.0ms-1 were tested on the proposed wind turbine. The experiments revealed that the turbine required a minimum wind speed of 3.9ms-1 to operate. According to the results, the proposed turbine achieved its maximum power output of 5.6W at a rotational speed of 65rpm when the wind speed was 7.0m/s. Additionally, voltage and current increased proportionately with increasing wind speed. The proposed system showed an average coefficient factor between 0.10 and 0.12. This portable wind turbine potentially revolutionizes industry while raising public awareness about clean and renewable energy.